Frequency, acceptability, and selection: A case study of clause-embedding. Issue 1 (4th November 2020) - White, Aaron Steven; Rawlins, Kyle
Abstract : We investigate the relationship between the frequency with which verbs are found in particular subcategorization frames and the acceptability of those verbs in those frames, focusing in particular on subordinate clause-taking verbs, such as think, want, and tell . We show that verbs' subcategorization frame frequency distributions are poor predictors of their acceptability in those frames—explaining, at best, less than 1 3 [10pt]article wasysym [substack]amsmath amsfonts amssymb amsbsy [mathscr]eucal mathrsfs pmc [Euler]upgreek empty -1.0in document \[ 13 \] document of the total information about acceptability across the lexicon—and, further, that common matrix factorization techniques used to model the acquisition of verbs' acceptability in subcategorization frames fare only marginally better.